The role of crop residues and agro-industrial by-products as animal feed resources in sub-Saharan Africa - Sibanda, S.; Said, A.N. (Nigeria Ministry of Agriculture and Water Resources, 1993)
The first part of the paper describes the predominant livestock production systems in sub-Saharan Africa. The second part discusses free resources available to the smallholders, feed resources available to the estate/large scale farmers, production levels of crop residues and agro-industrial by-products, nutritive value of crop residues, nutritive value of agro-industrial by-products, and improving utilization of crop residues and agro-industrial by-products. The last part examines the role of nitrogen supplementation, the role of readily fermentable energy supplementation, the role of forage and browse legumes, and the role of other methods of improving crop residue utilization. At the end of the paper strategies in developing improved feeding systems based on crop residue and agro-industrial by-products by smallholders in sub-Saharan Africa are presented.